Cannabis-derived products antagonize platinum drugs by altered cellular transport - Buchtova, Tereza; Beresova, Lucie; Chroma, Katarina; Pluhacek, Tomas; Beres, Tibor; Kaczorova, Dominika; Tarkowski, Petr; Bartek, Jiri; Mistrik, Martin (Biomedicine & pharmacotherapy, 2023)
Cannabinoids, a class of compounds derived from Cannabis sativa L., have recently become more widely accessible for public consumption in the form of diverse cannabis products, in parallel with weakening the measures that so far restricted their availability. The US Food and Drug Administration has approved several cannabis-derived drugs for management of various diseases as well as chemotherapy-induced nausea and vomiting. Besides the attenuation of adverse effects of chemotherapy, numerous reports about cannabinoid-mediated anticancer effects further motivate cancer patients to support their therapy with such products. Here we present a set of preclinical data with human cell culture models, suggesting that cannabidiol and cannabis extracts may effectively counteract the anticancer effects of the clinically widely used standard-of-care platinum-based drugs. We show that even low concentrations of cannabinoids reduced the toxicity of cisplatin, oxaliplatin, and carboplatin, an effect which was accompanied by decreased platinum adduct formation and a set of commonly used molecular markers. Mechanistically, our results excluded the possibility that the observed enhanced survival of cancer cells was mediated transcriptionally. Instead, trace metal analyses strongly indicate an inhibitory impact of cannabinoids on intracellular platinum accumulation, thereby implicating changes in cellular transport and/or retention of these drugs as the likely cause of the observed biological effects. Our study raises the possibility that the desirable effect of counteracting adverse effects of chemotherapy might, at least for some cannabinoids, reflect impaired cellular availability, and consequently attenuation of the anticancer effects of platinum drugs. DATA AVAILABILITY: All data supporting the conclusions are available in the article and supplementary files. Raw data are available upon request from the corresponding author.
Keywords: agonisté kanabinoidních receptorů; Analgesics; Hallucinogens; kanabidiol; Cannabis; halucinogeny; Cannabinoids; Platinum-based drugs; Platinum; kanabinoidy; léčivé přípravky; Humans; Cellular transport; Pharmaceutical Preparations; Drug therapy efficacy; Cannabidiol; Cannabinoid Receptor Agonists; platina; analgetika; lidé